From Distant to Public Reading - Dekel, Yael; Marienberg-Milikowsky, Itay (magazén, 2021)
From its very beginning, the term “distant reading” (Moretti 2000) was controversial, displacing ‘close reading’ by relying on literary histories and thereby reflecting on the entire global literary system. One of the weaknesses of this approach lies in its exclusive reliance on canonical and authoritative historiographies, one or two for each national literature, something which is bound to over-simplify the complexities of national literatures. As is known, Moretti’s proposal became a ‘slogan’ for Digital Humanities while algorithmic manipulation of texts has taken the place of reading literary (human) histories. Yet the problem of over-simplification remains, albeit differently. As an alternative, we offer a fusion approach, radicalising Moretti’s idea. In this article, we demonstrate how computer-based analysis of different readings carried out by many readers – not necessarily professionals – produces a relatively minute picture. Our case study will be the Hebrew novel, from its emergence in 1853 to the present day; a manageable corpus on which we gather information using questionnaires we have carefully created in our lab. Alongside the presentation of our approach, the actual research, and its initial findings, we will reflect theoretically on the conceptual benefits, as well as the limits, of public distance reading.